Non-random walk diffusion enhances the sink strength of semicoherent interfaces - A. Vattré (Nature Portfolio, 2016)
Materials resistant to radiation damage could improve the safety, efficiency and sustainability of nuclear energy. Here, the authors suggest that some materials and interfaces may be effective sinks for defects caused by this damage and propose that elastic interactions enhance sink strength.